Washington View: ESSA is more than the latest acronym on education's block. (March 2016) - Ferguson, Maria
For a law that took so long to get reauthorized, ESSA is a fairly predictable response to both NCLB and the Obama administration's efforts to make its mark despite Congressional gridlock. Accountability requirements for ESSA are similar to the waivers and starkly different from NCLB. States now have far more autonomy to determine how schools are held accountable for student performance. And there are key differences in ESSA so waiver states too will need to revise their accountability systems to comply with the new requirements. Finally, in what was almost a surely a tit-for-tat move, ESSA also contains nearly four pages of prohibitions on what the Secretary of Education can and cannot do.